COMPARISON OF LEARNING OUTCOMES AND STUDENT LEARNING STYLES: A STUDY ON TRIGONOMETRIC COMPARISON OF RIGHT TRIANGLES - Palinussa, Anderson Leonardo; Tamalene, Hanisa; Lawalata, Edith Merlin (Universitas Labuhanbatu, 2024)
Poor knowledge of mathematical concepts leads to poor math learning outcomes among students. Good reasoning will equip students to explain and argue mathematically. Therefore, the purpose of this study is to determine the comparison of learning outcomes and learning styles of students on trigonometric comparison material in right triangles. The variables in this study are visual learning style, auditorial learning style, and kinesthetic learning style (VAK) as independent variables and math learning outcomes as dependent variables. The participants in this study amounted to 77 people who came from the tenth grade, majoring in mathematics and natural sciences. The data used in this research is quantitative. Quantitative data is data in the form of numbers obtained from the results of a questionnaire consisting of 21 questions and mathematics learning outcomes received after working on a description question with as many as 3 numbers. The data analysis technique in this study is using the Mann Whitney-U test. The results of the survey obtained 23 or 29.9% of students with visual learning styles, 41 or 53.2% of students with auditory learning styles, and 13 or 16.9% of students with kinesthetic learning styles. The average learning outcome of students with a visual learning style is 70.09, students with an auditorial learning style are 71.72, and students with a kinesthetic learning style are 69.29. Based on the results of the analysis using SPSS 26.0, the significance value of each paired group of learning styles is more than the significance level α = 0.05. Therefore, there is no difference in math learning outcomes between students whose learning styles are visual, auditory, and kinesthetic.